Morbidity analysis of youth due to call-up of the Tomsk region - S. V. Astankin (Бюллетень сибирской медицины, 2007)
The 2-fold increase of pre-conscription youth and youth due to call-up morbidity is noted in Russian Federation during past decade. While recruiting of troops, for about 60% of the youth due to call-up were attributed to the 1-st group of health. More than 40% of the youth can not bear exercise which occurs during military labor. Index of unfitness to military service increased from 5.5 to 35% in the West Siberian regions. Armed forces are recruited with significant share of subjects having signs of protein - energetic insufficiency. All this necessitates studying condition of health and physical development of pre-conscription youth and youth due to call-up aimed at assessing causes of aggravated health and developing preventive measures in this category of mens population of the country.